2014
DOI: 10.5897/jdoh2013.0105
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessments of white-spot lesions treated with NaF plus tricalcium phosphate (TCP) toothpastes using synchrotron radiation micro computed tomography (SR micro-CT)

Abstract: Synchrotron radiation micro-computed tomography (SR micro-CT), considered superior to standard polychromatic micro-CT techniques, was used to assess the densities of bovine enamel white-spot lesions (WSL) treated in a 10-day pH cycling model with either: (A) Clinpro Tooth Crème (0.21% NaF plus TCP), (B) Clinpro 5000 (1.1% NaF plus TCP) or (C) Tom's of Maine (0% NaF) dentifrice. Each day consisted of four 2 min treatments, one 4 h acid challenge (pH=5.0), and immersion in artificial saliva (pH=7.0) between thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…2,4,12 A previous study using synchrotron radiation micro computed tomography to access the densities of bovine enamel WSL suggested Clinpro 5000, which contains 1.1% NaF, delivered remineralization benefits at the surface of the WSLs better than the 0.21% Clinpro Tooth Crème. 13 Since penetration of fluoride into enamel is limited and decreases exponentially with enamel depth, it might be possible that the functionalized TCP present in the Clinpro dentifrices helps extend the depth of fluoride penetration, and therefore lesion remineralization. 14 Notably, several in vitro studies have demonstrated the beneficial effect of fTCP on WSLs prevention and remineralization.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,12 A previous study using synchrotron radiation micro computed tomography to access the densities of bovine enamel WSL suggested Clinpro 5000, which contains 1.1% NaF, delivered remineralization benefits at the surface of the WSLs better than the 0.21% Clinpro Tooth Crème. 13 Since penetration of fluoride into enamel is limited and decreases exponentially with enamel depth, it might be possible that the functionalized TCP present in the Clinpro dentifrices helps extend the depth of fluoride penetration, and therefore lesion remineralization. 14 Notably, several in vitro studies have demonstrated the beneficial effect of fTCP on WSLs prevention and remineralization.…”
Section: Discussionmentioning
confidence: 99%